2020
DOI: 10.1177/0019793920981055
|View full text |Cite
|
Sign up to set email alerts
|

Altruism and Burnout: Long Hours in the Teaching Profession

Abstract: This article explores why many public school teachers work substantially more hours than required by contract, given that the elasticity of their earnings with respect to their hours is close to zero. The author introduces a theoretical framework for public-sector employees in which high levels of effort can indicate either altruism (for intrinsically motivated employees) or low productivity (for low-ability employees). Because intrinsically motivated employees derive higher utility from working in the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This is consistent with reports of many teachers experiencing discomfort with remote teaching technology (Kraft et al, 2021) and accounts that delivering online or hybrid instruction is more taxing on teachers (Kaufman & Diliberti, 2021). High hours are likely driven by the demands of mastering new technologies and learning platforms and of switching between different delivery modes mid-year and are also in line with prior research suggesting that intrinsic motivation drives some teachers to work longer hours than required by contract (Gicheva, 2020), as teachers have been expressing concerns about student engagement and learning during the pandemic (Kaufman & Diliberti, 2021).…”
Section: Discussionsupporting
confidence: 65%
“…This is consistent with reports of many teachers experiencing discomfort with remote teaching technology (Kraft et al, 2021) and accounts that delivering online or hybrid instruction is more taxing on teachers (Kaufman & Diliberti, 2021). High hours are likely driven by the demands of mastering new technologies and learning platforms and of switching between different delivery modes mid-year and are also in line with prior research suggesting that intrinsic motivation drives some teachers to work longer hours than required by contract (Gicheva, 2020), as teachers have been expressing concerns about student engagement and learning during the pandemic (Kaufman & Diliberti, 2021).…”
Section: Discussionsupporting
confidence: 65%
“…In summary, part-time teachers, on the one hand, do a significant amount of unpaid overtime, presumably because they want to perform their duties to high professional quality standards. Gicheva ( 68 ) emphasized altruism and a pro-social attitude as important reasons for regular unpaid overtime work among teachers. On the other hand, they give up a significant part of their salary and their future pension and accept poorer career opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…PRAE affords meaningful alignment of altruism, the research-identified, predominant personal value of those who enter the teaching profession [14], [15]; with Lave and Wenger's "legitimate peripheral participation" [16] (p. 29) to invoke the support and sense of belonging to the profession via an authentic connection to the greater community of practice [16], [17]. Framing this paradigm in an actionable fashion supports the individual both in the classroom and beyond through the direct connection to a greater sense of cohesion and shared purpose within the community of practice of educational professionals, despite physical separation of time and location.…”
Section: The Core Of Prae: Professional Reciprocal Altruism In Educationmentioning
confidence: 99%
“…Many teachers immerse themselves in the field of education with no focus on conditions of service but are motivated by the desire to enhance the lives of others; this context highlights a dichotomy present in the literature on altruism. While it is defined in terms of action and behavior [14], [8] it is reported by educators as a value, a guiding desire, "something that is wanted and needed but at the same time something that is necessary" [23] (p. 103).…”
Section: Altruism Definedmentioning
confidence: 99%